Analisis Pengembangan Instrument Evaluasi Tarkib dan Kosakata pada Materi Al-Hiwayah Kelas VIII dalam Buku Bahasa Arab - Jefri Hasibuan; Hikmah Hikmah; Nasrin Hasibuan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper discusses the importance of developing tarkib (grammatical structure) and vocabulary evaluation instruments in learning Arabic, which is a crucial aspect in understanding and composing meaningful sentences. Tarkib learning includes exercises in underlining fi'il and fa'il, converting ismiyyah sentences to fi'liyah numbers, filling in blanks and selecting answers in parentheses, completing sentences, identifying the type of amount. Vocabulary learning includes practice in pronouncing vocabulary according to pictures, writing vocabulary based on pictures and filling in blank sentences. This article also outlines the different levels of mastery of tarkib, from beginner to advanced. It is emphasized that effective and adaptive evaluation instruments are needed to measure students' abilities objectively, so as to improve students' linguistic competence and logical thinking skills.